Further explorations of possibilities, methodologies of the future and rogue traders - Jack, Lisa (Proceedings of Pragmatic Constructivism, 2015)
This presentation continues the discussion begun in May 2014 on the use of pragmatic constructivism and the actor reality construction framework in the analysis of financial crime.  Here, I examine one aspect, which is the use of the work of Barbara Adam on actors’ concepts of future time to develop an empirical framework for researching possibilities.  This is applicable to any empirical study using actor reality perspectives, but I am particularly interested in how rogue traders and their employers envisage and act on the possibilities open to them.